2022
DOI: 10.1002/jum.15955
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Normal Reference Values for Meniscal Extrusion Using Ultrasonography During the Different Range of Motion

Abstract: Objectives It is essential to know the normal extrusion measures in order to detect pathological ones. In this study, we aimed to define some normal reference values for meniscal extrusion in the normal knees during different ranges of motion. Methods The amount of anterior and posterior portion of meniscal extrusion among 21 asymptomatic volunteers (42 knees) were tracked in 0, 45, and 90° of knee flexion using an ultrasound machine. The repeated measures analysis of variance (ANOVA) was used to show the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Table 1 shows some of the cases of AS diagnosed with odontoid fractures. As demonstrated in that table, type II odontoid fracture, which was the most common type in the general population [12] , [13] , was more common among the cases with AS relative to other types of odontoid fractures. Also, it is worth mentioning that low-energy traumas, especially falling, were the major cause of odontoid fractures in patients with AS.…”
Section: Discussionmentioning
confidence: 77%
“…Table 1 shows some of the cases of AS diagnosed with odontoid fractures. As demonstrated in that table, type II odontoid fracture, which was the most common type in the general population [12] , [13] , was more common among the cases with AS relative to other types of odontoid fractures. Also, it is worth mentioning that low-energy traumas, especially falling, were the major cause of odontoid fractures in patients with AS.…”
Section: Discussionmentioning
confidence: 77%
“…In an ultrasound-based study, Kawaguchi et al (2012) showed that physiologic loading causes mild meniscal extrusion. Another ultrasound study demonstrated that the posterior portion experiences greater extrusion than the anterior portion, particularly as regards the medial meniscus (Sharafat Vaziri et al, 2022). Additionally, research has explored meniscal displacements and 3D morphological changes under knee weight-bearing and early flexion conditions in healthy adults, utilizing MRI (Liu et al, 2021).…”
Section: Figurementioning
confidence: 99%
“…Mechanical loading can significantly deform the menisci in knee extension; however, this effect is limited during knee flexion (Liu et al, 2021). In contrast, anteroposterior mobility commonly increases with the rise of knee flexion motion (Sharafat Vaziri et al, 2022). For this reason, the data concerning lateromedial displacement (X) appear to be more informative.…”
Section: Figurementioning
confidence: 99%
“…HLM is usually underdiagnosed due to unspecific symptoms and often a normal physical examination and magnetic resonance imaging (MRI) of the afflicted patients [2,3,38,47]. Unlike routine knee examinations, which reveal no abnormalities, it is reported that placing the patient's knee in the figureof-4 position can reproduce the same symptoms, helping to confirm the HLM diagnosis [3].…”
Section: Introductionmentioning
confidence: 99%